Spectral Bodies, Dystopian Cities: Literature and Economy in Portuguese-speaking Southern Africa, 1986-2012 - Waller, Thomas (2022)
Drawing from recent work at the intersection of world-systems analysis and materialist theories of world literature, this thesis argues that literary production in Portuguese-speaking southern Africa has developed distinctive aesthetic idioms that critically respond to crises of global capitalism and related failures in postcolonial governance. Focusing on spectral effects in Mozambican literature, and images of dystopia in Angolan fiction, I posit an elective affinity between the heightening of irrealist modes of signification in these two social contexts and the cyclical rhythms of the capitalist world-economy. Where existing studies have overwhelmingly read the elaboration of spectral and dystopian aesthetics in Angola and Mozambique as an index for the trajectory of the post-independence Marxist-Leninist state, I contend that these genres of writing rather function to register a world-systemic horizon that both surpasses and includes more locally determined, national realities. Taking the world- economic downturn and subsequent neoliberal ‘boom’ period of the 1980s, 1990s and early 2000s as a periodising framework, I thus demonstrate that the spike in spectral and dystopian fictions in the two states directly corresponds to the shifting local/global relations born out ofthe fraught passage between two phases of long-wave capitalist accumulation. This more expansive approach to the literature and economy of Portuguese-speaking southern Africa identifies a structural homology in the literary production of Angola and Mozambique that suggests comparison with texts produced at analogous yet historically specific moments across the long spiral of capitalist history, such as in mid-twentieth century Latin America. While the thesis thus engages in an exegesis of Latin American fiction typically labelled ‘magical realist’, it ultimately argues that the Warwick Research Collective’s development of the category of critical irrealism is a more suitable rubric through which to study the literature of Portuguese-speaking southern Africa.